N-PETG composite functional master batch as well as preparation method and application thereof
By using N-PETG composite functional masterbatch in refrigerator liner materials, the problems of poor heat resistance, aging resistance and mechanical properties of the materials have been solved, realizing the preparation of low-cost, high-performance refrigerator liner materials with excellent heat resistance, acid resistance and mechanical properties.
Patent Information
- Application Number
- CN202510861771.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2025-10-17
AI Technical Summary
Existing refrigerator liner materials have problems such as poor heat resistance, aging resistance and mechanical properties, high cost and complex processing technology.
By using N-PETG composite functional masterbatch, replacing 1,4-cyclohexanediethanol (CHDM) with neopentyl glycol (NPG), and adding lubricants, UV absorbers, and antioxidants, and employing reasonable raw material ratios and process settings, an N-PETG composite material with excellent dispersion performance, heat resistance, mechanical properties, and color fastness was prepared.
It achieves low cost and simple processing of materials, and has excellent heat resistance, acid resistance, high and low temperature cycling performance and aesthetics. Its performance is close to that of C-PETG composite materials, but the cost is reduced by about 40%.
Smart Images

Figure BDA0005467586000000111 
Figure BDA0005467586000000121
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of high polymer functional material modification, and particularly relates to an N-PETG composite functional master batch and a preparation method and application thereof. BACKGROUND
[0002] Currently, the commonly used refrigerator liner materials are polyurethane (PU) foaming materials, high-impact polystyrene (HIPS), polypropylene (PP), ABS (acrylonitrile-butadiene-styrene copolymer) and polycarbonate (PC) materials. These materials often have problems such as poor heat resistance, easy aging, low surface hardness, poor appearance, and high raw material prices.
[0003] PETG is a transparent amorphous copolyester, which is a product of melt copolymerization and polycondensation of terephthalic acid (PTA), ethylene glycol (EG) and a third monomer. The mechanical strength of PETG is better than that of HIPS, and the products made of PETG can better withstand external impact and pressure and are not easy to break when impacted, and can better maintain the integrity of the products. PETG has excellent resistance to a variety of chemical substances, including acids, bases, organic solvents, etc., and its performance and appearance are less likely to be affected when contacting these substances. In a humid environment or when in contact with water, the performance of PETG decreases less, and its service life is longer. PETG is an environmentally friendly material, which has less impact on the environment during production, use and disposal, does not produce harmful substances, meets environmental protection requirements, can be recycled and reused, and is conducive to resource conservation and environmental protection.
[0004] According to the difference of the third copolymer monomer, PETG can be divided into two types of C-PETG modified by 1,4-cyclohexane dimethanol (CHDM) and N-PETG modified by neopentyl glycol (NPG). C-PETG has more excellent chemical resistance, heat resistance and transparency, and is widely used in the markets of sheet, sheet, high-performance shrink film, bottle and profile, which can meet the requirements of most products for appearance. However, N-PETG has poor performance, but has the characteristics of low price and excellent processing performance.
[0005] CN119432014A discloses a material for making a refrigerator liner plate, which can improve the impact performance and heat resistance of the plate by adding a modified material to C-type PETG and aluminum powder. However, the disclosed refrigerator liner plate still needs to add aluminum powder to improve the heat insulation performance and appearance quality of the material, and the overall cost is high.
[0006] There are still problems of poor heat resistance, poor aging resistance, poor mechanical properties, high cost and complex processing technology in the prior art. Therefore, how to provide a new composite material with low raw material cost, simple processing and good heat resistance, aging resistance and excellent mechanical properties has become a problem to be solved at present. SUMMARY
[0007] To solve the above technical problems, the application provides an N-PETG composite functional master batch and a preparation method and application thereof. The N-PETG composite functional master batch provided by the application has the advantages of excellent dispersing performance, heat resistance, mechanical properties and high color fastness. The application also provides an N-PETG composite material. Through reasonable raw material ratio and process setting, the heat resistance, acid resistance, high and low temperature cycle performance, mechanical properties and appearance aesthetics of the N-PETG composite material are improved. Compared with the traditional composite material preparation process, the raw materials are more inexpensive and easy to obtain, and the process is green and environmentally friendly during processing and use. The N-PETG composite material has good application prospect in the refrigerator liner material.
[0008] To achieve this purpose, the application adopts the following technical solutions:
[0009] In a first aspect, the application provides an N-PETG composite functional master batch. The preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 35-70 parts, pigment 25-60 parts and auxiliary agent 1-5 parts by weight.
[0010] For example, the N-PETG carrier 35-70 parts can be 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts or 70 parts, etc.; the pigment 25-60 parts can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts or 60 parts, etc.; and the auxiliary agent 1-5 parts can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts, etc.
[0011] The N-PETG material obtained by replacing 1,4-cyclohexanedimethanol (CHDM) with neopentyl glycol (NPG) in the application. The introduction of NPG monomer in N-PETG destroys the symmetrical structure of polyethylene terephthalate molecular chain, slows down the crystallization rate of the material, reduces the crystallinity of the material, and increases the toughness of the material. The N-PETG composite functional master batch prepared by using N-PETG as a carrier has excellent dispersing performance, heat resistance, mechanical properties and high color fastness.
[0012] Preferably, the alcohol molar ratio content of neopentyl glycol monomer in the N-PETG carrier is 15-30%, for example, it can be 15%, 20%, 25% or 30%.
[0013] Preferably, the intrinsic viscosity of the N-PETG carrier is 0.56-0.8 dl / g, for example, it can be 0.56 dl / g, 0.6 dl / g, 0.65 dl / g, 0.7 dl / g, 0.75 dl / g or 0.8 dl / g.
[0014] Preferably, the auxiliary agent comprises any one or a combination of at least two of a lubricant, an ultraviolet light absorber or an antioxidant.
[0015] Preferably, the auxiliary agent comprises 1-4 parts by weight of the lubricant, for example, 1 part, 2 parts, 3 parts or 4 parts.
[0016] Preferably, the auxiliary agent comprises 0.1-0.5 parts by weight of the ultraviolet light absorber, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part or 0.5 part.
[0017] Preferably, the auxiliary agent comprises 0.1-0.5 parts by weight of the antioxidant, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part or 0.5 part.
[0018] Preferably, the pigment comprises dimethyl dichlorosilane modified white carbon black.
[0019] Preferably, the lubricant comprises an organic fatty lubricant.
[0020] The addition of the lubricant in the present application can make the pigment and other auxiliary agents uniformly dispersed in the material, reduce the internal friction between the molecules of the material, thereby improving the flow performance of the material and increasing the solubility of the carrier resin and the pigment.
[0021] Preferably, the ultraviolet light absorber comprises any one or a combination of at least two of a salicylate ultraviolet light absorber, a benzophenone ultraviolet light absorber, a benzotriazole ultraviolet light absorber, a substituted acrylonitrile ultraviolet light absorber or a triazine ultraviolet light absorber.
[0022] Preferably, the antioxidant comprises any one or a combination of at least two of a hindered phenol antioxidant, a phosphite antioxidant or a thiodipropionic acid diester.
[0023] The addition of the antioxidant in the present application can delay or inhibit the progress of the polymer oxidation process, thereby delaying the aging of the composite material and prolonging its service life.
[0024] In a second aspect, the present application provides a preparation method of the N-PETG composite functional master batch as described in the first aspect, the preparation method comprising the following steps:
[0025] (1) mixing the N-PETG carrier with the auxiliary agent to obtain a premix;
[0026] (2) mixing the premix with the pigment, and extruding and granulating to obtain the N-PETG composite functional master batch.
[0027] Preferably, the mixing in step (1) is carried out at a rotation speed of 150-300 rpm, for example, it can be 150 rpm, 200 rpm, 250 rpm or 300 rpm.
[0028] Preferably, the temperature of the mixing in step (1) is 40-50℃ (for example, it can be 40℃, 42℃, 44℃, 46℃, 48℃ or 50℃), and the mixing time is 15-75 min (for example, it can be 15 min, 30 min, 45 min, 60 min or 75 min).
[0029] Preferably, the mixing and extrusion granulation in step (2) are carried out in a twin-screw extruder.
[0030] Preferably, the temperature of each zone of the twin-screw extruder is as follows: the temperature of the first zone is 20-30℃, the temperature of the second zone is 180-200℃, the temperature of the third zone is 205-215℃, the temperature of the fourth zone is 210-220℃, the temperature of the fifth zone is 215-225℃, the temperature of the sixth zone is 215-225℃, the temperature of the seventh zone is 220-230℃, the temperature of the eighth zone is 225-235℃, the temperature of the ninth zone is 225-235℃, the temperature of the tenth zone is 225-235℃, the temperature of the eleventh zone is 215-225℃, and the temperature of the twelfth zone is 215-225℃.
[0031] For example, 20-30℃ can be 20℃, 22℃, 24℃, 26℃, 28℃ or 30℃; 180-200℃ can be 180℃, 185℃, 190℃, 195℃ or 200℃; 205-215℃ can be 205℃, 206℃, 208℃, 210℃, 212℃, 214℃ or 215℃; 210-220℃ can be 210℃, 212℃, 214℃, 216℃, 218℃ or 220℃; 215-225℃ can be 215℃, 216℃, 218℃, 220℃, 222℃, 224℃ or 225℃; 220-230℃ can be 220℃, 222℃, 224℃, 226℃, 228℃ or 230℃; 225-235℃ can be 225℃, 226℃, 228℃, 230℃, 232℃, 234℃ or 235℃.
[0032] Preferably, the die temperature of the twin-screw extruder is 210-240℃ (for example, it can be 210℃, 215℃, 220℃, 225℃, 230℃, 235℃ or 240℃), and the screw rotation speed is 100-200 rpm (for example, it can be 100 rpm, 120 rpm, 140 rpm, 160 rpm, 180 rpm or 200 rpm).
[0033] In a third aspect, the present invention provides an N-PETG composite material, wherein the raw materials for preparing the N-PETG composite material include, by weight, a substrate and the N-PETG composite functional masterbatch as described in the first aspect.
[0034] Preferably, the raw materials for preparing the N-PETG composite material include 90-95 parts by weight of a base material and 5-10 parts by weight of an N-PETG composite functional masterbatch.
[0035] Among them, 90-95 parts of the substrate can be, for example, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts or 95 parts; 5-10 parts of the N-PETG composite functional masterbatch can be, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.
[0036] Preferably, the substrate comprises an N-PETG substrate.
[0037] Preferably, the alcohol molar ratio of the neopentyl glycol monomer in the N-PETG substrate is 15-30%, for example, 15%, 20%, 25% or 30%.
[0038] Preferably, the intrinsic viscosity of the N-PETG substrate is 0.56-0.8 dl / g, for example, 0.56 dl / g, 0.6 dl / g, 0.65 dl / g, 0.7 dl / g, 0.75 dl / g or 0.8 dl / g.
[0039] In a fourth aspect, the present invention provides a method for preparing the N-PETG composite material as described in the third aspect, characterized in that the preparation method comprises the following steps:
[0040] The raw materials for preparing the N-PETG composite material are melt-blended and extruded into granules to obtain the composite functional masterbatch.
[0041] Preferably, the melt blending temperature is 200-220°C, for example, 200°C, 205°C, 210°C, 210°C or 220°C.
[0042] In a fifth aspect, the present invention provides a use of the N-PETG composite material as described in the third aspect in a refrigerator liner material.
[0043] Compared with the prior art, the present invention has at least the following beneficial effects:
[0044] (1) The present invention provides an N-PETG composite functional masterbatch. The introduction of NPG monomer destroys the symmetrical structure of the polyethylene terephthalate molecular chain, slows down the crystallization rate of the material, reduces the crystallinity, increases the transparency of the material, and increases the toughness, so that the masterbatch has excellent dispersion performance, heat resistance, mechanical properties and high color fastness.
[0045] (2) The application provides an N-PETG composite material, which has improved heat resistance, acid resistance, high and low temperature cycle performance and mechanical performance through reasonable raw material ratio and process setting.
[0046] (3) The N-PETG composite material provided by the application can be directly physically mixed with the N-PETG composite functional master batch for processing and production, without the need of being processed into mixed material particles through double-screw granulation, so that the preparation cost of the material is greatly reduced, and the production efficiency is improved.
[0047] (4) The N-PETG composite material provided by the application is white in color, and has excellent appearance when applied to a refrigerator liner material.
[0048] (5) The N-PETG composite material provided by the application can basically achieve a technical effect similar to that of a C-PETG composite material, but the preparation cost is reduced by about 40%. DETAILED DESCRIPTION
[0049] In order to facilitate the understanding of the application, the application is illustrated by the following preparation examples and application examples. It should be understood by those skilled in the art that the preparation examples and application examples are only used to help understand the application, and should not be regarded as a specific limitation on the application.
[0050] In the following specific embodiments of the application, the specific information of the materials used is as follows:
[0051] 1. N-PETG base material, HG-2701, purchased from Jiangsu Honggang Petrochemical Co., Ltd.;
[0052] 2. N-PETG carrier, HG-2701, purchased from Jiangsu Honggang Petrochemical Co., Ltd.;
[0053] 3. Lubricant, SHN1007A, purchased from Jiangsu Honggang Petrochemical Co., Ltd.;
[0054] 4. Pigment, TS-610, purchased from Cabot;
[0055] 5. Ultraviolet light absorber, UV-P, purchased from Liyanlong;
[0056] 6. Antioxidant, antioxidant 1010;
[0057] 7. Antioxidant, antioxidant 168.
[0058] Preparation Example 1
[0059] An N-PETG composite functional master batch, the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 52 parts, lubricant (SHN1007A) 2 parts, pigment (TS-610) 45.3 parts, ultraviolet light absorber (UV-P) 0.5 parts, antioxidant (1010) 0.1 parts and antioxidant (168) 0.1 parts by weight.
[0060] The preparation method of the N-PETG composite functional master batch includes the following steps:
[0061] The N-PETG carrier, lubricant (SHN1007A), ultraviolet light absorber (UV-P), antioxidant (1010) and antioxidant (168) are uniformly mixed in a high-speed mixer to obtain a premix, the rotation speed of the high-speed mixer is 250 rpm, the mixing temperature is 40℃, and the mixing time is 30 min, the premix is put into the main feeding port of the twin-screw extruder, the pigment (TS-610) is put into the side feeding hopper of the fifth zone to mix with the premix, and then the N-PETG composite functional master batch is obtained by extruding and granulating. The processing temperature of each zone of the twin-screw extruder is: the temperature of the first zone is 25℃, the temperature of the second zone is 190℃, the temperature of the third zone is 210℃, the temperature of the fourth zone is 215℃, the temperature of the fifth zone is 220℃, the temperature of the sixth zone is 220℃, the temperature of the seventh zone is 2225℃, the temperature of the eighth zone is 230℃, the temperature of the ninth zone is 230℃, the temperature of the tenth zone is 230℃, the temperature of the eleventh zone is 220℃, the temperature of the twelfth zone is 220℃, the temperature of the die is 220℃, the frequency of the main feeding port is 5HZ, and the rotation speed of the screw is 140 rpm.
[0062] Preparation Example 2
[0063] An N-PETG composite functional master batch, which is different from preparation example 1 in that the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 56 parts, lubricant (SHN1007A) 3 parts, pigment (TS-610) 40.5 parts, ultraviolet light absorber (UV-P) 0.3 parts, antioxidant (1010) 0.1 parts and antioxidant (168) 0.1 parts by weight.
[0064] Preparation Example 3
[0065] An N-PETG composite functional master batch, which is different from preparation example 1 in that the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 60 parts, lubricant (SHN1007A) 3 parts, pigment (TS-610) 36.3 parts, ultraviolet light absorber (UV-P) 0.4 parts, antioxidant (1010) 0.2 parts and antioxidant (168) 0.1 parts by weight.
[0066] Preparation Example 4
[0067] An N-PETG composite functional master batch, different from Preparation Example 1 in that the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 65 parts, lubricant (SHN1007A) 3 parts, pigment (TS-610) 31.4 parts, ultraviolet light absorber (UV-P) 0.4 parts, antioxidant (1010) 0.1 part, and antioxidant (168) 0.1 part by weight.
[0068] Preparation Example 5
[0069] An N-PETG composite functional master batch, different from Preparation Example 1 in that the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 35 parts, lubricant (SHN1007A) 4 parts, pigment (TS-610) 60 parts, ultraviolet light absorber (UV-P) 0.5 parts, antioxidant (1010) 0.2 parts, and antioxidant (168) 0.2 parts by weight.
[0070] Preparation Example 6
[0071] An N-PETG composite functional master batch, different from Preparation Example 1 in that the lubricant (SHN1007A) in the preparation raw materials of the N-PETG composite functional master batch is replaced with an equal amount of zinc stearate.
[0072] Comparative Preparation Example 1
[0073] An N-PETG composite functional master batch, different from Preparation Example 1 in that the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 25 parts, lubricant (SHN1007A) 2 parts, pigment (TS-610) 45.3 parts, ultraviolet light absorber (UV-P) 0.1 parts, antioxidant (1010) 0.1 parts, and antioxidant (168) 0.1 parts by weight.
[0074] Comparative Preparation Example 2
[0075] An N-PETG composite functional master batch, different from Preparation Example 1 in that the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 80 parts, lubricant (SHN1007A) 2 parts, pigment (TS-610) 45.3 parts, ultraviolet light absorber (UV-P) 0.5 parts, antioxidant (1010) 0.1 parts, and antioxidant (168) 0.1 parts by weight.
[0076] Comparative Preparation Example 3
[0077] An N-PETG composite functional master batch, different from the preparation example 1 in that the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 52 parts, lubricant (SHN1007A) 2 parts, pigment (TS-610) 45.3 parts, ultraviolet light absorber (UV-P) 0.1 part, antioxidant (1010) 0.1 part and antioxidant (168) 0.1 part by weight.
[0078] Comparative preparation example 4
[0079] An N-PETG composite functional master batch, different from the preparation example 1 in that the preparation raw materials of the N-PETG composite functional master batch include N-PETG carrier 22.9 parts and pigment (TS-610) 74.8 parts by weight.
[0080] Comparative preparation example 5
[0081] A C-PETG composite functional master batch, the preparation raw materials of the C-PETG composite functional master batch include C-PETG carrier (C-PETG, K2012, purchased from SK Chemical) 52 parts, lubricant (SHN1007A) 2 parts, pigment (TS-610) 45.3 parts, ultraviolet light absorber (UV-P) 0.5 parts, antioxidant (1010) 0.1 part and antioxidant (168) 0.1 part by weight.
[0082] The preparation method of the C-PETG composite functional master batch includes the following steps:
[0083] The C-PETG carrier, lubricant (SHN1007A), ultraviolet light absorber (UV-P), antioxidant (1010) and antioxidant (168) are uniformly mixed in a high-speed mixer to obtain a premix, the rotation speed of the high-speed mixer is 250 rpm, the mixing temperature is 40℃, and the mixing time is 30 min, the premix is put into the main feeding port of the twin-screw extruder, the pigment (TS-610) is put into the side feeding hopper of the fifth zone to mix with the premix, and then the C-PETG composite functional master batch is obtained by extruding and granulating. The processing temperature of each zone of the twin-screw extruder is: the temperature of the first zone is 25℃, the temperature of the second zone is 190℃, the temperature of the third zone is 210℃, the temperature of the fourth zone is 215℃, the temperature of the fifth zone is 220℃, the temperature of the sixth zone is 220℃, the temperature of the seventh zone is 2225℃, the temperature of the eighth zone is 230℃, the temperature of the ninth zone is 230℃, the temperature of the tenth zone is 230℃, the temperature of the eleventh zone is 220℃, the temperature of the twelfth zone is 220℃, the temperature of the die is 220℃, the frequency of the main feeding port is 5HZ, and the rotation speed of the screw is 140 rpm.
[0084] Application example 1
[0085] An N-PETG composite material, raw materials for preparing the N-PETG composite material include N-PETG base material 93 parts and N-PETG composite functional masterbatch prepared in Preparation Example 1 7 parts by weight.
[0086] The preparation method of the N-PETG composite material includes the following steps: melt blending N-PETG composite functional masterbatch 7 parts with N-PETG base material 93 parts at 210°C, and then extruding and granulating to obtain the composite functional masterbatch.
[0087] Application Examples 2-6 and Comparative Application Examples 1-4
[0088] An N-PETG composite material, which is different from Application Example 1 in that the N-PETG composite functional masterbatch prepared in Application Examples 2-6 and Comparative Preparation Examples 1-5 is used to replace the N-PETG composite functional masterbatch in the application example.
[0089] Comparative Application Example 5
[0090] A C-PETG composite material, raw materials for preparing the C-PETG composite material include C-PETG base material 93 parts and C-PETG composite functional masterbatch prepared in Comparative Preparation Example 5 7 parts by weight.
[0091] The preparation method of the C-PETG composite material includes the following steps: melt blending C-PETG composite functional masterbatch 7 parts with C-PETG base material (C-PETG, K2012, purchased from SK Chemical) 93 parts at 210°C, and then extruding and granulating to obtain the composite functional masterbatch.
[0092] Comparative Application Example 6
[0093] A commercially available HIPS material, 8265, purchased from Dow.
[0094] Test method
[0095] The N-PETG composite materials provided by Application Examples 1-6 and Comparative Application Examples 1-4 and the C-PETG composite materials and HIPS materials provided by Comparative Application Examples 5-6 are injection molded into sheet 1 of 80mm×10mm×4mm and sheet 2 of 50mm×50mm×6mm, respectively, for the following tests:
[0096] (1) Color: The color of sheet 2 is tested according to the material visual color as the judgment standard;
[0097] (2) Heat distortion: Sheet 1 is tested according to ASTM D256, and the test pressure is 0.45MPa;
[0098] (3) Ball pressure deformation: the sheet 2 is tested according to GB / T 5169.21-2017;
[0099] (4) High-low temperature cycle: the sheet 2 is tested according to GB / T 2423.22-2012, the low temperature is-40℃, the high temperature is 65℃, the holding time is 4h, and the cycle number is 10 times.
[0100] Test results
[0101] The N-PETG composite materials provided by application examples 1-6 and comparative application examples 1-4 and the C-PETG composite materials and HIPS materials provided by comparative application examples 5-6 are tested for performance, and the test results are shown in Table 1:
[0102] Table 1
[0103]
[0104]
[0105] It can be seen from the test results that:
[0106] (1) It can be seen from application examples 1 to 6 that the N-PETG composite material prepared by the application has excellent temperature resistance, ball pressure deformation resistance and high-low temperature cycle resistance, and the color of the material product meets the requirements, and the test results meet the detection requirements of the refrigerator liner material.
[0107] (2) It can be seen from application example 1 and comparative application examples 1-2 that the application can obtain good appearance and excellent mechanical performance by reasonable formula design, and too little or too much N-PETG carrier is not conducive to the temperature resistance, ball pressure deformation resistance and high-low temperature cycle resistance of the material.
[0108] (3) It can be seen from application example 1 and comparative application examples 3-4 that when the composite functional master batch prepared by the application lacks lubricant, ultraviolet light absorber and antioxidant, the prepared N-PETG composite material cannot achieve good heat deformation resistance and high-low temperature cycle resistance technical effect.
[0109] (4) It can be seen from application example 1 and comparative application example 5 that the N-PETG composite material provided by the application can basically achieve the technical effect of little difference with the C-PETG composite material in performance, but the preparation cost is reduced by about 40%.
[0110] (6) It can be seen from the application examples and comparative application example 6 that the N-PETG composite material containing N-PETG composite functional master batch improves the heat resistance and mechanical properties of the material compared with the traditional HIPS material.
[0111] The applicant states that the above description is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto, and it should be understood by those skilled in the art that any changes or replacements within the technical scope disclosed by the present application can be easily thought out by those skilled in the art, and all of them fall within the protection scope and disclosure scope of the present application.
Claims
1. An N-PETG composite functional masterbatch, characterized in that, The raw materials for preparing the N-PETG composite functional masterbatch include 35-70 parts of N-PETG carrier, 25-60 parts of pigment and 1-5 parts of auxiliary agent in parts by weight.
2. N-PETG composite functional masterbatch according to claim 1, is characterized in that, The alcohol molar ratio content of the neopentyl glycol monomer in the N-PETG carrier is 15-30%; Preferably, the intrinsic viscosity of the N-PETG carrier is 0.56-0.8 dl / g.
3. The N-PETG composite functional masterbatch according to claim 1 or 2, characterized in that, The auxiliary agent includes any one of a lubricant, an ultraviolet light absorber or an antioxidant, or a combination of at least two thereof; Preferably, the auxiliary agent includes 1-4 parts by weight of lubricant; Preferably, the auxiliary agent includes 0.1-0.5 parts by weight of ultraviolet light absorber; Preferably, the auxiliary agent includes 0.1-0.5 parts by weight of antioxidant.
4. The N-PETG composite functional masterbatch according to any one of claims 1 to 3, characterized in that The pigment includes dimethyldichlorosilane-modified white carbon black; Preferably, the lubricant comprises an organic lipid lubricant; Preferably, the ultraviolet light absorber includes any one or a combination of at least two of a salicylate ultraviolet light absorber, a benzophenone ultraviolet light absorber, a benzotriazole ultraviolet light absorber, a substituted acrylonitrile ultraviolet light absorber or a triazine ultraviolet light absorber; Preferably, the antioxidant comprises any one of a hindered phenol antioxidant, a phosphite antioxidant or a thiodipropionate diester, or a combination of at least two thereof.
5. A method for preparing the N-PETG composite functional masterbatch according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) N-PETG carrier is mixed with auxiliary agent to obtain premix; (2) The premix is mixed with the pigment, and the N-PETG composite functional masterbatch is obtained by extrusion granulation.
6. The preparation method of N-PETG composite functional masterbatch according to claim 5, wherein The mixing in step (1) is carried out at a rotation speed of 150-300 rpm; Preferably, the mixing temperature in step (1) is 40-50° C., and the mixing time is 15-75 min; Preferably, the mixing and extrusion granulation in step (2) are carried out in a twin-screw extruder; Preferably, the temperatures of the zones of the twin-screw extruder are: zone 1 temperature 20-30°C, zone 2 temperature 180-200°C, zone 3 temperature 205-215°C, zone 4 temperature 210-220°C, zone 5 temperature 215-225°C, zone 6 temperature 215-225°C, zone 7 temperature 220-230°C, zone 8 temperature 225-235°C, zone 9 temperature 225-235°C, zone 10 temperature 225-235°C, zone 11 temperature 215-225°C, and zone 12 temperature 215-225°C; Preferably, the die head temperature of the twin-screw extruder is 210-240° C., and the screw speed is 100-200 rpm.
7. An N-PETG composite material, characterized in that The raw materials for preparing the N-PETG composite material include a substrate and the N-PETG composite functional masterbatch according to any one of claims 1 to 4.
8. The N-PETG composite material according to claim 7, wherein The raw materials for preparing the N-PETG composite material include 90-95 parts by weight of a base material and 5-10 parts by weight of the N-PETG composite functional masterbatch according to any one of claims 1 to 5; Preferably, the substrate comprises an N-PETG substrate; Preferably, the alcohol molar ratio content of the neopentyl glycol monomer in the N-PETG substrate is 15-30%; Preferably, the intrinsic viscosity of the N-PETG substrate is 0.56-0.8 dl / g.
9. A method for preparing the N-PETG composite material as claimed in claim 7 or 8, characterized in that: The preparation method comprises the following steps: The raw materials for preparing the N-PETG composite material are melt-blended and extruded into granules to obtain the N-PETG composite material.
10. Use of the N-PETG composite material according to claim 7 or 8 in refrigerator liner materials.
Citation Information
Patent Citations
Material for manufacturing refrigerator liner plate, refrigerator liner and refrigerator
CN119432014A